REHABILITASI TANAH TAILING DENGAN MENGGUNAKAN BEBERAPA JENIS PUPUK ORGANIK YANG DITANAMI JAGUNG MANIS (ZEA MAYS SACCHARATA STURT.) - Nisar Armanto Ridjal; Tommy D. Sondakh; Ronny Nangoi (COCOS, 2018)
ABSTRACK This research was conducted to observe the changes of physical properties and responses of sweet corn (Zea mays saccharata Sturt.) planted on Tatelu's tailings soil. The reserch conducted at the UNSRAT Experimental Garden in Wailan Village, Tomohon City on July 2018 to February 2019. The research used Completely Randomized Design (CRD) as research methodology which consisted five treatments. The treaments were: A = 300 kg / ha of phonska fertilizer + 0 tons / ha of organic fertilizer, B = 300 kg / ha of phonska fertilizer + 50 tons / ha of goat manure, C = 300 kg / ha of phonska fertilizer + 40 tons / ha of fertilizer organic plus + 10 tons / ha goat manure, D = 300 kg / ha phonska fertilizer + 30 tons / ha organic fertilizer + 20 tons / ha goat manure, E = 300 kg / ha phonska fertilizer + 30 tons / ha organic fertilizer plus + 20 tons / ha of goat manure. Each treatment was repeated four times to obtain 20 experimental pots. Sweet corn plants as indicators. Parameters observed included: 1) Sweet corn cobs weight, 2) Oven dry weight of sweet corn plants 3) Analysis of soil physical properties after harvest: organic-C, Soil Pemeality and porosity. The field experiment used a polybag pot with a completely randomized design consisting of five treatments with four replications. The data obtained will be analyzed by variance. If F-count is greater than F-table (F count> F table), then the data will e analyzed with the smallest real difference test (BNT 5%). The results showed that the combination of organic matter in soil tailings had a significant effect on organic-C, porosity, and permeability, but it had no significant effect on cob weight, and plant dry weight, but tended to provide a greater value compared with no organic matter. Organic materials and plus organic materials tend to be better than goat manure to rehabilitate tailings. Â Keywords: Rehabilitation of tailings, and kinds of organic materials.